Philosophy, crime, and criminology - Arrigo, Bruce A.; Williams, Christopher R., 1972- (Critical perspectives in criminology., 2006)
Philosophy, Crime, and Criminology represents the first systematic attempt to unpack the philosophical foundations of crime in Western culture. Utilizing the insights of ontology, epistemology, aesthetics, and ethics, contributors demonstrate how the reality of crime is informed by a number of implicit assumptions about the human condition and unstated values about civil society. Charting a provocative and original direction, editors Bruce A. Arrigo and Christopher R. Williams couple theoretically oriented chapters with those centered on application and case study. In doing so, they develop an insightful, sensible, and accessible approach for a philosophical criminology in step with the political and economic challenges of the twenty-first century. Revealing the ways in which philosophical conceits inform prevailing conceptions of crime, Philosophy, Crime, and Criminology is required reading for any serious student or scholar concerned with crime and its impact on society and in our lives.